2007
DOI: 10.1590/s0102-311x2007000600018
|View full text |Cite
|
Sign up to set email alerts
|

Triagem auditiva em hospital público de Belo Horizonte, Minas Gerais, Brasil: deficiência auditiva e seus fatores de risco em neonatos e lactentes

Abstract: IntroduçãoA audição é o principal sentido responsável pela aquisição da fala e linguagem da criança; o déficit desta função pode provocar prejuízo não só no desenvolvimento da linguagem, mas também, no aspecto social, emocional e cognitivo. A perda auditiva é uma alteração muito prevalente no período neonatal. Estudos revelam uma incidên-cia em torno de 1 a 3 e de 20 a 50 por mil nascimentos, respectivamente, entre bebês saudáveis e provenientes de Unidades de Terapia Intensiva (UTI) 1,2 .O Joint Committee on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
15
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 11 publications
5
15
1
4
Order By: Relevance
“…The relationship between low birth weight and failed NHS and/or hearing loss has been shown in the literature 29,30 . Authors said that the lower the birth weight, the greater the chances of failure in the NHS 32,33 , which was not observed in this study. No relationship between the NHS results and gestational age agrees with evidenced by other researchers 29 .…”
Section: Discussioncontrasting
confidence: 61%
“…The relationship between low birth weight and failed NHS and/or hearing loss has been shown in the literature 29,30 . Authors said that the lower the birth weight, the greater the chances of failure in the NHS 32,33 , which was not observed in this study. No relationship between the NHS results and gestational age agrees with evidenced by other researchers 29 .…”
Section: Discussioncontrasting
confidence: 61%
“…A total of 798 infants and newborns were evaluated, of whom 468 (25.6%) presented at least one indicator of risk for hearing loss. The most prevalent risk indicators of newborns were family history, represented by 25%, equal to that found in our study (25.6%) 13 . Another study conducted in a public hospital in São Paulo, Brazil, in 2009, found the percentage of neonates with risk indicators to be similar to those of Minas Gerais 14 .…”
Section: Discussionsupporting
confidence: 59%
“…Tiensoli et al 13 identified the prevalence of hearing impairment in a public children's hospital in Belo Horizonte, Minas Gerais, Brazil. A total of 798 infants and newborns were evaluated, of whom 468 (25.6%) presented at least one indicator of risk for hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, 47.8% of the newborns underwent NHS with up to 30 days of life and 52.2%, aged over 30 days (12) . In another study, the chronological age of children ranged from 3 days to 9 months, with 80.6% of the population being screened before 3 months of age (13) . It is known that the Brazilian reality falls short from what it advocated by the NHSP of developed countries, however, taking into consideration premature infants and/or those with long periods of hospitalization, the examination can be performed until the third month of life of the infants in corrected age (10) .…”
Section: Discussionmentioning
confidence: 99%
“…In view of the presented arguments, it was verified that this reality contributes in order to make the diagnostic process to occur later than the one recommended. In the Brazilian literature, it is possible to observe the late diagnosis, as in a study that was conducted in Belo Horizonte (MG), in which the average relation between the suspicion and confirmation of the hearing loss was of 4.2 months (13) . Another study showed that the average waiting time to start the use of the individual sound amplifier device (ISAD) was 26.5 months (15) .…”
Section: Discussionmentioning
confidence: 99%